Analysis the Attractions and Facilities of Marandang Traditional Culinary Festival against the Motivation of Visitors in Padang City - Gagih Pradini; Fitri Agustiani; Anisa Putri Kusumaningrum (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The Marandang Traditional Culinary Festival is one of the festivals created by the The Marandang Traditional Culinary Festival is a festival created by the Padang City Tourism Office to motivate visitors outside the city with the aim of introducing the hereditary culture of cooking rendang. This study aims to determine the analysis of the Attractiveness and Facilities of the Marandang Traditional Culinary Festival on the Motivation of Visitors. In taking this sample for this study using purposive sampling. Data taken in this study through primary data by distributing questionnaires to 76 respondents. The analytical technique used is the tests contained in SPSS 23. The results of this study indicate that the variables of Attractiveness, Facilities, as well Attractions and Facilities together produce data that affect the motivation of visitors in the city of Padang.